Exercise as a Component of Enhanced Recovery After Surgery (ERAS): A Narrative Review - Kasperska, Klaudia; Arciszewski, Kamil; Stenzel, Paweł; Niewola, Karolina; Szumiło, Jakub; Walczak, Dominika; Orda, Karolina; Hariasz, Natalia; Markiv, Mariana; Słowik, Michał (Quality in Sport, 2026)
Background. Enhanced Recovery After Surgery (ERAS) protocols represent a multimodal, evidence-based approach aimed at reducing surgical stress, minimizing complications, and accelerating postoperative recovery. While ERAS pathways have demonstrated significant improvements in perioperative outcomes, the role of exercise—encompassing both prehabilitation and early postoperative mobilization—remains insufficiently standardized and inconsistently implemented despite growing evidence supporting its clinical benefits. Aim. The aim of this narrative review was to evaluate the role of exercise as a component of ERAS protocols, with particular emphasis on prehabilitation and early postoperative mobilization, and to identify current limitations and propose a structured framework for integrating physical activity into perioperative care. Material and methods. A narrative literature review was conducted using PubMed, Scopus, and Web of Science databases. The search strategy included keywords such as “ERAS”, “prehabilitation”, “exercise”, “physical activity”, and “early mobilization”. Eligible studies included randomized controlled trials, systematic reviews, meta-analyses, and observational studies related to perioperative exercise. The selected literature was analyzed qualitatively to identify key mechanisms, clinical outcomes, and implementation barriers. Results. Exercise interventions were shown to improve functional capacity, enhance metabolic resilience, and reduce postoperative complications. Prehabilitation was associated with increased cardiorespiratory fitness and improved tolerance to surgical stress, particularly in high-risk and oncological patients. Early postoperative mobilization contributed to improved pulmonary function, reduced thromboembolic risk, and faster recovery of functional independence. However, significant variability was observed in exercise protocols, including differences in timing, intensity, and implementation, highlighting a lack of standardization within ERAS pathways. Key barriers included patient-related factors, organizational constraints, and limited integration of exercise into clinical practice. Conclusions. Exercise represents a critical yet underutilized component of ERAS protocols. Its structured integration, including prehabilitation and early mobilization, has the potential to significantly improve perioperative outcomes and recovery. The development of standardized, evidence-based exercise protocols and enhanced interdisciplinary collaboration are essential to optimize implementation and maximize clinical benefits.